The development of Tatra car company in normalization period - Pospíšil, Jakub (2011)
This bachelor thesis is focused on the development of Kopřivnice car company in normalization period. In the first part of my work I completed history of Tatra company from begin to primary researched period, this in the context of economic and political situation of this period. The second part specifically analyzes the car factory during the seventies. Especially the capital construction, which was started after decision to lead Tatra into the program of multilateral international specialization of the COMECON countries, results and competitiveness of cars compare to production in the west part of the World. The eim of my thesis is to determine factors, which influenced progress in researched period both at national and international level.